Управління ресурсним потенціалом для забезпечення сталого розвитку підприємства - Сторожук, Олександр Анатолійович; Storozhuk, Oleksandr (ЦНТУ, 2024)
Метою роботи є обґрунтувати теоретико-методичні підходи та розробити практичні рекомендації щодо управління ресурсним потенціалом підприємства для забезпечення його сталого розвитку. The purpose of the work is to substantiate theoretical and methodological approaches and to develop practical recommendations for managing the resource potential of an enterprise to ensure its sustainable development.
Management of resource potential for ensuring sustainable development of the enterprise
Keywords: ресурсний потенціал; сталий розвиток підприємства; управління ресурсами; resource potential; sustainable development of the enterprise; resource management